Classroom Management at MTs Pondok Pesantren Sabilul Hasanah Banyuasin - Ibrahim; Desi Maulita; Beni Saputra (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
This article discusses the Management of Classes during the Covid 19 Pandemic at MTs Sabilul Hasanah Banyuasin. With the main problem being the source of the problem, as we know that to achieve the learning objectives good Class Management is needed, but in the current situation due to the Covid 19 pandemic, not all schools implement face-to-face learning policies but online, the authors found in schools MTs Pondok Pesantren Sabilul Hasanah applies a face-to-face learning policy but in accordance with existing health protocol procedures. In this study, the author uses qualitative descriptive research. The data collection techniques in this study were through observation, interviews, and documentation. While the techniques used in data analysis are data reduction, data presentation, and drawing conclusions, so that the data can be known well, and for the validity of the data using triangulation. The results showed that the implementation of class management during the covid 19 pandemic at Madrasah Tsanawiyah Sabilul Hasanah had been carried out well, in the implementation of class management activities it was divided into two, namely student arrangements including behavior, discipline, passion for learning, group dynamics and facility arrangements. including ventilation, lighting, comfort, seating, and student placement. From the two arrangements for class management activities, he has done well. And as for the requirements for the implementation of face-to-face learning during the COVID-19 pandemic in accordance with the health protocol, it has met the requirements that have been set.